Cirrophorus species (Annelida: Polychaeta: Paraonidae) in the Sea of Marmara, with description of a new species - Erdoğan-Dereli, Deniz; Çinar, Melih Ertan; Dağli, Ertan (Zootaxa, 2017)
This paper deals with specimens of Cirrophorus collected from the depths ranging from 3 to 500 m in 2012 and 2013 in the Sea of Marmara, Turkey. Among the material, one new species and two already known species were found. The new species is mainly characterized by having long and clavate notopodial postchaetal lobes in the branchial region; red speckles near nuchal organs; and a very long branch of lyrate chaetae (4 times longer than the shorter one). A recently described species, Cirrophorus nikebianchii, was found at the majority of soft-bottom stations. All species found in the area were described and discussed.